Pemanfaatan Sumberdaya Perikanan Berbasis Kearifan Lokal Di Wilayah Pesisir Kabupaten Kutai Timur - Juliani Juliani (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2015)
This study aimed to examine the characteristics of fishing communities in the coastal areas of East Kutai Regency. The fishing communities form a distinctive community and dependent on the existence of natural resources in the vicinity. There are various forms of local wisdom possessed by the fishing community with regard to their main activity is fishing activities. Various forms of local wisdom includes beliefs and taboos when performing catch activities, ethics and rules on fishing activities, techniques and technologies applied catchs, as well as the practices and traditions of management and use of natural resources. Location of the study was 7 districts in the coastal area of East Kutai Regency has a fairly large fishery potential fishery households with large amounts of which are Teluk Pandan, South Sangatta, North Sangatta, Bengalon, Kaliorang Sangkulirang and Sandaran. This study basically using sampling techniques are not random (non-probability) that a purposive sampling technique. Determination of respondents with purposive sampling method based certain considerations that are taken based on the purposed of research. Resource management in the form of: a) the existence of indigenous institutions that play a role in regulating the management and utilization of marine resources and coastal fisheries, b) the establishment of a group of fishermen and farmers institutional accompanied by coaching and mentoring more effective in cooperation with governments, companies and research institutions, c) the existence of institutional gathering /yasinan fisherman woman who has the role of venture capital can both strengthen fisheries, d) determination agreement fishing area and type of fishing gear that is allowed for certain waters